Peran Guru dalam Meningkatkan Kemampuan Calistung Siswa Kelas Rendah di MI Tarbiyatul Akhlaq Wedoroanom Driyorejo - Dia Silfianah; Barudin (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2022)
This research aims to find out what the role of teachers is in increasing the calistung of lower class students at MI Tarbiyatul Akhlaq Wedoroanom. In this research, researchers use qualitative research. This research will produce descriptive data in the form of words, not numbers, involving existing events. The data collection techniques used were interviews, observation and documentation. Data analysis techniques are carried out using data collection, reduction, data presentation and conclusions. Checking the validity of the data uses method triangulation and source triangulation. These problems were discussed through qualitative research carried out at MI Tarbiyatul Akhlaq Wedoroanom. The results of the research show that in improving the calistung ability of low class students at MI Tarbiyatul Akhlaq, the teacher as a class manager provides appropriate management of the learning space by providing positive energy to students, in managing students the teacher provides concentration for students, and in activating students provides a process good and comfortable learning so as to create a pleasant atmosphere for students. Students who have low ability in calistung receive special teaching after school.